GENETIC EXCHANGES OF INTEINS BETWEEN PRASINOVIRUSES (PHYCODNAVIRIDAE). (10th August 2012) - Clerissi, Camille; Grimsley, Nigel; Desdevises, Yves
<x xml:space="preserve">Abstract</x> Phylogenetic diversity in the Phycodnaviridae (double‐stranded DNA viruses infecting photosynthetic eukaryotes) is most often studied using their DNA polymerase gene (PolB). This gene and its translated protein product can harbor a selfish genetic element called an "intein" that disrupts the sequence of the host gene without affecting its activity. After translation, the intein peptide sequence self‐excises precisely, producing a functional ligated host protein. In addition, inteins can encode homing endonuclease (HEN) domains that permit the possibility of lateral transfers to intein‐free alleles. However, no clear evidence for their transfer between viruses has previously been shown. The objective of this paper was to determine whether recent transfers of inteins have occurred between prasinoviruses (Phycodnaviridae) that infect the Mamiellophyceae, an abundant and widespread class of unicellular green algae, by using DNA sequence analyses and cophylogenetic methods. Our results suggest that transfer among prasinoviruses is a dynamic ongoing process and, for the first time in the Phycodnaviridae family, we showed a recombination event within an intein.